A Student’s Guide to Practical Work in Soil Science - Muršec, Mateja (University of Maribor Press, 2022)
The student’s guide is intended for foreign students choosing Soil science subject at UM. It contains the basics of the geological composition of the lithosphere, classification, mineral composition, and recognition of various rocks. Students are guided through the use of proper equipment and methods of sampling, transportation, preservation, and sample preparation prior to further analysis. Field work and laboratory procedures for determining various physical (soil structure, texture, bulk density, porosity, soil moisture, soil colour) and chemical (soil reaction, organic matter content, nitrogen, phosphorus, and potassium content) characteristics of soil quality are described. Finally, it helps students to describe the soil profile with an accurate description of the general soil horizons and the determination of the soil type.